Patient-derived organoid facilitating personalized medicine in non-small cell lung cancer: two case reports - Qin, Lili; Wang, Shasha; Li, Liping; Qin, Haifeng (Frontiers in Oncology, 2025)
Patients with brain metastases from lung cancer exhibit rapid disease progression and a poor prognosis, underscoring an urgent need for effective therapeutic strategies. Drug sensitivity testing using patient-derived organoids (PDOs) has emerged as a promising tool for guiding clinical treatment decisions. Here, we report two cases of non-small cell lung cancer (NSCLC) with brain metastases where treatment guided by PDO-based drug sensitivity screening aided in disease control. Case 1 involved a patient with an EGFR exon 19 deletion. The corresponding PDO model demonstrated sensitivity to a combination of pemetrexed, carboplatin, and osimertinib, but insensitivity to osimertinib monotherapy. Following this guidance, the patient achieved a partial response (PR) to the triplet regimen and was subsequently de-escalated to maintenance therapy. The patient’s disease remained stable at the time of this report. Case 2 involved a patient with a complex EML4-ALK fusion variant 3 (E6:A20) and a novel NRXN1-ALK fusion (N19:A20). The patient had progressed on multiple lines of therapy, including alectinib and lorlatinib. The PDO model showed sensitivity to brigatinib but insensitivity to ensartinib. Subsequent treatment with brigatinib induced a PR that was sustained for 5.8 months; the patient survived for a total of 9 months following the initiation of this PDO-guided therapy. These two cases suggests that PDOs derived from primary and metastatic lesions may help optimize treatment regimens for patients with lung cancer brain metastases, thereby enabling personalized therapy and potentially improving survival outcomes.